EFEKTIVITAS PELAYANAN DENGAN SISTEM JEMPUT BOLA DALAM PENGURUSAN IZIN MENDIRIKAN BANGUNAN (IMB) PADA DINAS PEKERJAAN UMUM DAN TATA RUANG KABUPATEN KONAWE - Mus Emil,ST (Jurnal Manajemen Rekayasa (Journal of Engineering Management), 2019)
This study aims to find out and examine how the effectiveness of services with ball pick-up systems inmanaging building permits (IMB) at the Konawe District Public Works and Spatial Office. This study used a sample of 96 respondents. The analysis technique used is descriptive statistical analysis techniques and using Microsoft Office Excel. The results of the study show that. Supporting effectiveness of service factors are (a) Employees of Konawe District Public Works and Spatial Planning who are experienced and have the ability / expertise and (b) Availability of Complete Facilities. Licensing services with the Pick-up system are Licensing Services that are formed with the aim of bringing licensing closer to the community. Service Effectiveness with Ball Pick- Up System in Building Management Permit (IMB) the result of the effectiveness level is 3.36 or with very effective criteria with an effectiveness percentage of 83.93% and then with good implementation the service of Building Permit (IMB) with Pickup system The ball is also carried out by building and controlling buildings so that the focus is on the realization of budget revenues in local tax revenues which have increased even exceeding the target. Keywords: Service Effectiveness and Building Construction Permits